Analisis Persepsi Masyarakat Terhadap Perbankan Syariah di Desa Maracang Kabupaten Purwakarta - Salma Fauziah; Jalaludin Jalaludin; Ahmad Ali Sopian (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
As a people of Maracang Village, the increase in Islamic bank institutions in Maracang Village has no effect at all on people's interest in saving at Islamic banks. It is caused by the lack of public knowledge of Islamic banking institutions. This study aims to determine the object of perception of the Maracang village community towards Islamic banking, to determine the sensory tools of the Maracang village community's perception of Islamic banking, and to determine the attention of the Maracang village community on Islamic banking products. This type of research is field research or case study with a qualitative descriptive approach. The data collection technique was done by triangulation (combined). The result showed that the people in Maracang Village still did not have an interest in saving at Islamic banks because of the objects, senses and people's attention to Islamic banking institutions. In terms of objects, most of them did not know all the aspects that exist in Islamic banks; it’s about savings and financing products, also the unstrategic locations of the bank. They thought that services at conventional banks were still better than Islamic banks. In terms of senses of society, the services of Islamic banks were inadequate, the human resources were not good. The objects and sense of people of Maracang Village to the perception of Islamic banking affected the bad attention.